A Study of Ideal Facial Proportions in Attractive Thai Women - Sri-in, A-yothaya; Sucontphunt, Tanasai (Thai Journal of Science and Technology, 2024)
The objectives of this study were to study the ideal facial proportions for Thai women’s beauty standards and to find ideal facial proportions that are appropriate for Thai women. The average facial proportions which were calculated from various pictures of Thai female actors, singers, and influencers on social media, gathered from online sources, were used as the appropriate proportions. The 13 images of the face which were simulated by using the appropriate proportions and other facial proportions were grouped into 4 groups according to the degree of proportional adjustment. The respondents were then asked to rate their score for the attractiveness of each facial image. The results showed that the average attractiveness score for an ideal face image was the highest score. To compare the differences, a non-parametric test was used to compare the mean values of the attractiveness rating of each group. The comparison found that the mean values for each group were statistically different.